При b = - 5[latex]( \frac{7}{15b} - \frac{2}{3b} ): \frac{b ^{2} }{2} [/latex]

При b = - 5[latex]( \frac{7}{15b} - \frac{2}{3b} ): \frac{b ^{2} }{2} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]b=-5\\\\( \frac{7}{15b} - \frac{2}{3b} ): \frac{b^2}{2} = \frac{7-10}{15b} \cdot \frac{2}{b^2} =- \frac{3}{15b} \cdot \frac{2}{b^2} =- \frac{1}{5b} \cdot \frac{2}{b^2} =- \frac{2}{5b^3} =\\\\=- \frac{2}{5\cdot (-5)^3} = \frac{2}{5^4} = \frac{2}{625} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы